Moringa oleifera Flour Fermentation as Feed Additive on Egg Quality in Mojosari Ducks with Different Storage Period - Rahmaniar Larasati; Sri Hidanah; Muchammad Yunus; Widya Paramita Lokapirnasari; Emy Koestanti Sabdoningrum; Mohammad Anam Al Arif (Universitas Airlangga, 2023)
Eggs are widely consumed by Indonesian people. High market demand will cause breeders to increase egg productivity and quality. Moringa oleifera leaves addition to the feed could increase egg production. Moringa leaf flour has high crude fiber, so it needs to be fermented. Fermentation aims to reduce crude fiber and increase crude protein. This study aims to determine the effect of using fermented Moringa leaf flour on the egg yolk index of the Haugh Unit and the color of the Mojosari's duck egg yolk with different shelf life. 60 ducks divided into four treatment groups, namely P0 without fermented Moringa leaf flour addition, P1 with 0.5% Moringa leaf flour fermentation, P2 with 1% Moringa leaf flour fermentation, and P3 with 1.5%. Moringa leaf flour fermentation. The results showed that the addition of 1.5% fermented Moringa leaf flour (P3) gave the highest average value for the egg yolk index, Haugh Unit, and egg yolk color with different storage period. Providing fermented Moringa oleifera leaf flour at 1.5% as a feed additive had the highest influence on increasing the egg yolk index, haugh unit value, and egg yolk color of mojosari ducks with different storage period.